Digital Prescription and Dispensation of Medications - Severo, Liverson Paulo Furtado; Martina, Jean Everson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246608, 2025)
Context: In Brazil, the prescription and dispensing of medications remain largely manual, relying on physical documents. This approach poses challenges for security, traceability, and regulatory compliance, especially for controlled substances. Problem: Manual systems are insufficient for tracking medication dispensing, preventing misuse, and ensuring interoperability between healthcare providers and pharmacies. Solution: This study proposes a system that integrates the FHIR interoperability standard, adapted to produce self-contained documents, with JAdES digital signatures for secure and authentic prescription records. Blockchain is used to enable traceability and control over medication dispensing through an immutable record of transactions. Method: The research employed a Proof of Concept (PoC) methodology to validate the proposed system, focusing on analyzing the current manual processes and proposing a digital solution to address identified gaps. This PoC was conducted in a controlled laboratory environment to simulate real-world scenarios and test the integration of FHIR, JAdES signatures, and Blockchain technologies to evaluate the system’s functionality and compliance with regulatory requirements. Results: The system successfully generated secure, self-contained digital prescriptions and used Blockchain to trace and control medication dispensing. It improved regulatory compliance and addressed interoperability issues by eliminating external dependencies. Contributions: This work advances healthcare information systems by combining interoperability standards, electronic signatures, and Blockchain to digitize and secure critical processes, addressing key challenges in medication management.